Towards Improved Access to Secondary Education in Kenya: A Focus on In-School-Factors that Hinder Effective Transition from Primary Schools - Odhiambo, Fredrick; Shinali, Mary Consolata; Koech, Peter (International Journal of Education and Research, 2015)
This study sought to investigate some in-school factors that influence learner access to secondary schools after completion of primary schooling in Narok North District and to suggest strategies that could improve the level of access. The study was conducted in public primary and secondary schools in Narok North District, Narok Countyusing descriptive survey.Stratified sampling technique was used to select the schools from the three Divisionsfor equal representation. Individual schools and respondents to participate in the studywere selected using simple random sampling. All the twenty four (24) primary school head teachers, four (4) secondary school principals and three (3) Quality Assurance and Standards Officers in the selected Divisions were purposively selected to participate. A total of 68 class eight pupils and 44 form one students were randomly chosen from the sampled schools. The study had a total of 143 participants. Data were collected using questionnaires and an interview schedule. A pilot test was done in one secondary and three primary schools. The study revealed forced repetition, little emphasis placed on co-curricular activities, inadequate facilities in schools, acute under staffing as major impediments to open access to secondary level of education in the area. The study recommends the need to build and improve infrastructure and facilities to existing schools, enhancement of strict curriculum supervision in the schools to ensure adherence to government policies and directive sand proper reinforcement and monitoring of teacher preparation and content delivery to provide a learning environment that is child-centered, gender-sensitive and disability friendly.
Keywords: Access; child labour; Disability-friendly environment; Gender-sensitive; School-based factors; Transition